On crisis and commitment in social sciences - "Dube, S.C." (New Delhi, 1983)
The seminal essays in Crisis and commitment in the Social Sciences examine critically, and in depth, the predicament of the social science enterprise in India and the Third World. Largely emulative in its concepts and research techniques, the practice of these disciplines has become an esoteric cult devoid of a social purpose. Professor Dube argues vigorously for restoration of purpose to the social sciences, for greater free play to endogenous creativity through their indigenization , and for building into them for greater relevance so that they enlarge mass consciousness and inform public policy.
Keywords: Social sciences .